Un système zonal de primes pour les travailleurs du Nord, un exemple de géographie appliquée - Hamelin, Louis-Edmond (Cahiers de géographie du Québec)

(untitled) (Département de géographie de l'Université Laval, 1970)
This study has been organized in three parts. First, there is a presentation of the main characteristics of the manpower in the Canadian North where there is a non adjustment between the demand and the supply of labour. Follow a review of the existing allowances regimes whose the most elaborated comes from the Treasury Board of Canada (1970 edition). Secondly, this paper deals with the rationale of the northern allowance itself and its global impact on the economy. A quantitative definition is given of the nordicity (northerness). Finally, the author suggests a System of package deal with only one indemnity for environment, cost of living and others excessive northern expenses. The level of this global bonus is given by the degree of nordicity (physical and human) in the site where the worker has his living. Any employee should receive a year around 900 dollars in the Lower Middle North but 2 100 dollars in the Far North. To discourage the great mobility of the workers, the basic indemnity grows with their persistance on the job. At last, to encourage the high qualified officers to go in the North, a special allowance may be given to them.